Researching lifelong learning participation through an interdisciplinary lens. Issue 3 (27th May 2017) - Boeren, Ellen
ABSTRACT: This paper explores the interdisciplinary nature of studies in the field of lifelong learning participation. Until recently, participation studies have been presented in a rather fragmented way, often drawing on insights from separate disciplines such as sociology or psychology. The complex nature of lifelong learning participation, however, urges scholars to go beyond this disciplinary fragmentation and to advance knowledge in an integrative way, through the construction of new interdisciplinary theories and the adoption of interdisciplinary research approaches. This paper discusses a new integrative theory and outlines a range of methodological challenges of working in interdisciplinary teams on interdisciplinary projects. Examples include understanding each other's disciplinary background, the need to combine different insights from sociology, psychology, learning providers and governments' policy decisions in multilevel models and the desire to adopt both quantitative and qualitative research methods.